Assessment of the Performance of Out-patient Acute Malnutrition Management in Children under 5 Years in the Northern Benin Setting - SOSSA, JÉRÔME CHARLES; PARAÏSO, NOEL MOUSSILIOU; AGUEH, VICTOIRE DAMIENNE AGOSSI; AZANDJEME, COLLECTE SYLVIE; AGBEHONOU, Kokou Pascal; MONGBO, Virginie; MAKOUTODE, CODJO ABODOURIN ALBERT CHARLES PATRICK (My University, 2016)
Aims: To assess the performance of out-patient acute malnutrition management in children under 5 years. Study Design: Cross-sectional study. Place and Duration of Study: Northern Benin, health district of Djougou-Ouake-Copargo, from 1st to 30th June, 2014. Methodology: Fifteen functional out-patient malnutrition management centres (out the 27 existing) were included in the study. Data on acute malnutrition management were collected in thirty skilled health workers by using questionnaire and observation. Data were also collected in 296 children who suffered from acute malnutrition through medical records, reference documents and supervisions note books. The performance of out-patient acute malnutrition management was assessed through three components “input/resources”, “process” and “results” using predetermined score of two scales seeking for achievement of criterions according to WHO reference for the evaluation of the performance of the health system. Results: The performance of the out-patient management of acute malnutrition in the health district was rated low. Conclusion: The performance of out-patient management of acute malnutrition in the health district was suboptimal. Adequate monitoring of malnourished treated child and a greater mobilization of community volunteers in the active search of drop out patients are required to improve the performance of out-patient management of acute malnutrition in health district of Djougou-Copargo- Ouaké in Benin.
Keywords: Out-patients acute malnutrition management; performance; health district; Benin